Smartphone use is a risk factor for pediatric dry eye disease according to region and age: a case control study. Issue 1 (December 2016) - Moon, Jun; Kim, Kyoung; Moon, Nam
Abstract Background In 2014, the overall rate of smartphone use in Korea was 83 and 89.8 % in children and adolescents. The rate of smartphone use differs according to region (urban vs. rural) and age (younger grade vs. older grade). We investigated risk and protective factors associated with pediatric dry eye disease (DED) in relation to smartphone use rate according to region and age. Methods We enrolled 916 children and performed an ocular exam that included slit lamp exam and tear break-up time. A questionnaire administered to children and their families consisted of video display terminal (VDT) use, outdoor activity, learning, and modified ocular surface disease index (OSDI) score. DED was defined based on the International Dry Eye Workshop guidelines (Objective signs: punctate epithelial erosion or short tear break-up time; subjective symptoms: modified OSDI score) We performed statistical analysis of risk factors and protective factors in children divided into groups as follows: DED vs. control, urban vs. rural, younger grade (1st to 3rd) vs. older grade (4th to 6th). Results A total of 6.6 % of children were included in the DED group, and 8.3 % of children in the urban group were diagnosed with DED compared to 2.8 % in the rural group (P = 0.03). The rate of smartphone use was 61.3 % in the urban group and 51.0 % in the rural group (P = 0.04). In total, 9.1 % of children in the older-grade group were diagnosed with DED compared to 4 % in the younger-grade group (P = 0.03). The rate of smartphone use was 65.1 % in older-grade children and 50.9 % in younger-grade children (P < 0.001). The mean daily duration of smartphone use was longer in the DED group than controls (logistic regression analysis, P < 0.001, OR = 13.07), and the mean daily duration of outdoor activities was shorter in the DED group than controls (logistic regression analysis, P < 0.01, OR = 0.33). After cessation of smartphone use for 4 weeks in the DED group, both subjective symptoms and objective signs had improved. Conclusions Smartphone use in children was strongly associated with pediatric DED; however, outdoor activity appeared to be protective against pediatric DED. Older-grade students in urban environments had DED risk factors (long duration of smartphone use), and a short duration of outdoor activity time. Therefore, close observation and caution are needed when older children in urban areas use smartphones.